A path to peace: A comparative study of practitioners' views of juvenile restorative justice in Chile, England, Italy, and Sweden. (January 2019) - Reyes-Quilodran, Claudia Andrea; LaBrenz, Catherine A; Donoso, Gabriela
Recent attention to juvenile delinquency has led to calls for alternative approaches for youth offenders that can reduce recidivism. This research analyzes how practitioners in Sweden, England, Italy, and Chile perceive the implementation of victim offender mediation (VOM). An emphasis is given to challenges and strategies that practitioners in Sweden, England, and Italy report, in order to provide a framework for implementation of VOM in a country in the early stages of implementation and consideration, such as Chile. An instrumental comparative case study design was used to compare the four cases of VOM implementation, conducting in-depth interviews in each country with key informants about the implementation process. The results suggest that practitioners are overwhelmingly satisfied with VOM in each European country, and that their experiences can be incorporated as lessons learned for practitioners in other countries seeking to implement VOM. Implications for adapting VOM to a different cultural context are described in the discussion, as well as a critical analysis of the need for more empirical evidence and further research on VOM and its underlying philosophy of social justice and accountability.